Tract sizes in miniaturized percutaneous nephrolithotomy: a systematic review from the European Association of Urology Urolithiasis Guidelines Panel - Ruhayel, Yasir; Knoll, Thomas (European urology, 2017)
Context: Miniaturized instruments for percutaneous nephrolithotomy (PNL), utilizing tracts sized ≤22 Fr, have been developed in an effort to reduce the morbidity and increase the efficiency of stone removal compared with standard PNL (>22 Fr). Objective: We systematically reviewed all available evidence on the efficacy and safety of miniaturized PNL for removing renal calculi. Evidence acquisition: The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Since it was not possible to perform a meta-analysis, the data were summarized in a narrative synthesis. Evidence synthesis: After screening 2945 abstracts, 18 studies were included (two randomized controlled trials [RCTs], six nonrandomized comparative studies, and 10 case series). Thirteen studies were full-text articles and five were only available as congress abstracts. The size of tracts used in miniaturized procedures ranged from 22 Fr to 4.8 Fr. The largest mean stone size treated using small instruments was 980mm2. Stone-free rates were comparable in miniaturized and standard PNL procedures. Procedures performed with small instruments tended to be associated with significantly lower blood loss, while the procedure duration tended to be significantly longer. Other complications were not notably different between PNL types. Study designs and populations were heterogeneous. Study limitations included selection and outcome reporting bias, as well as a lack of information on relevant confounding factors. Conclusions: The studies suggest that miniaturized PNL is at least as efficacious and safe as standard PNL for the removal of renal calculi. However, the quality of the evidence was poor, drawn mainly from small studies, the majority of which were single-arm case series, and only two of which were RCTs. Furthermore, the tract sizes used and types of stones treated were heterogeneous. Hence, the risks of bias and confounding were high, highlighting the need for more reliable data from RCTs. Patient summary: Removing kidney stones via percutaneous nephrolithotomy (PNL) using smaller sized instruments (mini-PNL) appears to be as effective and safe as using larger (traditional) instruments, but more clinical research is needed.
Gesehen am 05.11.2018